Small intestinal entrapment through a mesovarium ligament rent in a mare - Greenberg, Ji Ann; Hoff, Sydney; Rech, Raquel R (Brazilian Journal of Veterinary Pathology, 2025)
An 18-year-old, American Paint mare presented for acute colic for a suspected colon torsion. On presentation, the blood and abdominal lactate were 1.3 mmol/L (normal range 0-2 mmol/L) and 5.3 mmol/L (normal range <2 mmol/L), respectively. In the following morning, her blood and abdominal lactate increased to 7.3 mmol/L and 9.9 mmol/L. Due to uncontrollable pain, lack of a surgical option due to financial limitations, and increasing suspicion for a strangulating lesion, euthanasia was elected.